2014
DOI: 10.2147/ijn.s74868
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles inhibit cancer cell invasion and enhance antitumor efficiency by targeted drug delivery via cell surface-related GRP78

Abstract: Nanoparticles (NPs) which target specific agents could effectively recognize the target cells and increase the stability of chemical agents by encapsulation. As such, NPs have been widely used in cancer treatment research. Recently, over 90% of treatment failure cases in patients with metastatic cancer were attributed to resistance to chemotherapy. Surface-exposed glucose-regulated protein of 78 kDa (GRP78) is expressed highly on many tumor cell surfaces in many human cancers and is related to the regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
1
25
0
2
Order By: Relevance
“…For example, Wang et al demonstrated that ursolic acid NP inhibited cervical cancer migration through inducing apoptosis 21 . BSA-based GRP78 receptor-targeting NP have been shown to inhibit hepatocellular carcinoma (HCC) cell invasion via receptor-mediated binding 20 . While local metastasis is the hallmark and the root cause of the high brain cancer mortality, there has not been any attempt so far as published in public domain to study the effect of NP uptake on invasion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Wang et al demonstrated that ursolic acid NP inhibited cervical cancer migration through inducing apoptosis 21 . BSA-based GRP78 receptor-targeting NP have been shown to inhibit hepatocellular carcinoma (HCC) cell invasion via receptor-mediated binding 20 . While local metastasis is the hallmark and the root cause of the high brain cancer mortality, there has not been any attempt so far as published in public domain to study the effect of NP uptake on invasion.…”
Section: Discussionmentioning
confidence: 99%
“…4). There were existing studies describing the inhibition of invasion by using NP loaded with radioisotopes and chemotherapeutics on hepatocellular carcinoma and gastric cancer 20,63 , in which the cell invasions were inhibited by the cytotoxicity of the payload. In this study, pSiNP was not carrying any therapeutics, and the treatment did not hamper viability nor intracellular ATP content (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…153 155,156 GRP78 mAb-conjugated bovine serum albumin (BSA) loaded with 5-FU was developed to promote 5-FU into HCC cells and inhibit the adhesion, invasion, and metastasis of HCC, 157 which was verified by cell administrations. The AF-20 mAb has a high affinity for AF-20 antigen, which was found to distribute uniformly on 15/15 HCC tissues tested but was not evident on adjacent normal liver or in most normal human tissues.…”
mentioning
confidence: 99%
“…Aunque la función fisiológica de GRP78 en la superficie celular dista de ser totalmente comprendida, se ha obtenido evidencia de que GRP78 puede formar complejos con proteínas específicas en la membrana plasmática desencadenando señales involucradas en procesos oncogénicos como son: sobrevivencia, proliferación, invasión, metástasis y quimioresistencia (Zhao et al, 2015, Tsai et al, 2015. La unión de la forma activa de la proteína inhibidora de proteasas a 2 Macroblobulina a GRP78 en la membrana plasmática en la línea celular de cáncer de próstata 1-LN desencadena la proliferación y supervivencia de las células cancerosas a través de la activación de la vía PI3K/AKT , NF-kB y UPR (Misra et al, 2006).…”
Section: Respuesta Celular Al Estrés Upr (Unfolded Protein Response; unclassified